Load Flow Analysis of Dhaka Grid Using PSAT and ETAP and Performance Comparison with PGCB Data - Abdullah Alvi, Anas; Mannan, Mohammad Abdul (AIUB Journal of Science and Engineering (AJSE), 2019)
This paper deals with a load flow simulation of existing Dhaka Grid Circle of Bangladesh National Grid by using Power System Analysis Toolbox (PSAT) which is a free and open source software of MATLAB Simulink and Electrical Transient and Analysis Program (ETAP) software designed for simulation, operation, and automation of generation, distribution, and industrial power systems. All the data used to simulate were collected from Power Grid Company of Bangladesh (PGCB) and Load flow analysis was carried out using Newton Raphson method and simulated results were compared with PGCB Base Case Data. The network considered to simulate has 71 buses (400, 230 and 132 kV), 135 interconnecting lines, 32 generators, 47 loads and only 4 shunt capacitors as per the Dhaka grid circle system. Regarding the maximum demand of the load centers, total 5,525 MW load is connected in this system and the average grid generation in September, 2018 was 10,919.57 MW, though only 5988 MW of the total generation is enlisted in the Dhaka grid circle.